Effects of leptin on pedunculopontine nucleus (PPN) neurons - Beck, Paige (2013)
Leptin, a hormone that regulates appetite and energy expenditure, is increased in obese individuals, although these individuals often exhibit leptin resistance. Obesity is characterized by sleep/wake disturbances, such as excessive daytime sleepiness, increased REM sleep, increased nighttime arousals, and decreased percentage of total sleep time. Several studies have shown that short sleep duration is highly correlated with decreased leptin levels in both animal and human models. Arousal and rapid eye movement (REM) sleep are regulated by the cholinergic arm of the reticular activating system, the pedunculopontine nucleus (PPN). The goal of this project was to determine the role of leptin in the PPN, and thus in obesity-related sleep disorders. Whole-cell patch-clamp recordings were conducted on PPN neurons in 9- to 17-day-old rat brainstem slices. Leptin decreased action potential (AP) amplitude, AP frequency, and h-current (IH). These findings suggest that leptin causes a blockade of Na+ channels. Therefore, we conducted an experiment to test the effects of leptin on Na+ conductance. To determine the average voltage dependence of this conductance, results from each cell were equally weighted by expressing conductance as a fraction of the maximum conductance in each cell. INa amplitude was decreased in a dose-dependent manner, suggesting a direct effect of leptin on these channels. The average decrease in Na+ conductance by leptin was ~40 %. We hypothesize that leptin normally decreases activity in the PPN by reducing IH and INa currents, and that in states of leptin dysregulation (i.e., leptin resistance) this effect may be blunted, therefore causing increased arousal and REM sleep drive, and ultimately leading to sleep-related disorders.